The Effect Of Competency And Organizational Culture On Employee Performance At Serpong M-Town Signature Apartment - Rosadi, Eka; Santoso, Arief Budi (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
This study aims to investigate the influence of competence and organizational culture on individual performance in an organizational context. Strong competence and positive organizational culture are considered important factors in achieving superior performance in various work environments. This study uses a quantitative research method by collecting data through questionnaires distributed to employees at various levels in an organization. Data analysis techniques used include regression analysis to identify the relationship between competence variables and organizational culture on performance. The results of the study indicate that individual competence has a significant influence on their performance in the organization. The higher the level of competence, the higher the individual performance. In addition, a positive organizational culture also plays an important role in improving employee performance. Organizations with a culture that supports innovation, collaboration, and individual development tend to have better performance. This study has important implications for organizational management in human resource development and organizational culture management. Recognizing the importance of competence and positive organizational culture can help organizations improve their employee performance and achieve their strategic goals.